Mola: five-layer symmetrical pattern - Unidentified artist (Colorado State University. Libraries, 2016)
This very well sewn mola has five complete layers of cloth. Other signs of quality are small stitching, sharp points and even edges on each layer.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 5 layers (black, pink, maroon, orange, maroon); reverse and direct appliqué, embroidery.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama